Progress and Prospects of Mycorrhizal Fungal Diversity in Orchids - Li, Taiqiang; Yang, Wenke; Wu, Shimao; Selosse, Marc-André; Gao, Jiangyun (Frontiers in Plant Science, 2021)
Orchids form mycorrhizal symbioses with fungi in natural habitats that affects their seed germination, protocorm growth, and adult nutrition. An increasing number of studies indicates how orchids gain mineral nutrients and sometime even organic compounds from interactions with orchid mycorrhizal fungi (OMF). Thus, OMF exhibit a high diversity and play a key role in the life cycle of orchids. In recent years, high-throughput molecular identification of fungi has broadly extended our understanding of OMF diversity, revealing it to be a dynamic outcome co-regulated by environmental filtering, dispersal restrictions, spatiotemporal scales, biogeographic history, as well as the distribution, selection, and phylogenetic spectrum width of host orchids. Most of the results show congruent emerging patterns. Although it is still difficult to extend them to all orchid species or geographical areas, to a certain extent they follow the "everything is everywhere, but the environment selects" rule. This review provides an extensive understanding of the diversity and ecological dynamics of orchid–fungal association. Moreover, it promotes the conservation of resources and regeneration of rare or endangered orchids. We provide a comprehensive overview, systematically describing six field of research on orchid–fungal diversity: research methods of orchid–fungal interactions, primer selection in high-throughput sequencing, fungal diversity and specificity in orchids, difference and adaptability of OMF in different habitats, comparison of OMF in orchid roots and soil, and spatiotemporal variation patterns of OMF. Further, We highlight certain shortcomings of the current research methodologies and propose perspectives for future studies. This review emphasizes the need for more information on the four main ecological processes of dispersal, selection, ecological drift, and diversification, as well as their interactions, in the study of orchid–fungal interactions and OMF community structure.